Antiallodynic effect of intrathecal epigallocatechin-3-gallate due to suppression of reactive oxygen species - An, Sang Soon (The Korean Society of Anesthesiologists, 2014)
BACKGROUND: Green tea modulates neuropathic pain. Reactive oxygen species (ROS) are suggested as a key molecule in the underlying mechanism of neuropathic pain in the spinal cord. We examined the effect of epigallocatechin-3-gallate (EGCG), the major catechin in green tea, in neuropathic pain and clarified the involvement of ROS on the activity of EGCG. METHODS: Neuropathic pain was induced in male Sprague-Dawley rats by spinal nerve ligation (SNL). A polyethylene tube was intrathecally located. Nociceptive degree was estimated by a von Frey filament and expressed as a paw withdrawal threshold (PWT). To determine the role of ROS on the effect of EGCG, a free radical donor (tert-BuOOH) was pretreated before administration of EGCG. ROS activity was assayed by xanthine oxidase (XO) and malondialdehyde (MDA). RESULTS: SNL decreased the PWT compared to sham rats. The decrease remained during the entire observation period. Intrathecal EGCG increased the PWT at the SNL site. Intrathecal tert-BuOOH significantly decreased the effect of EGCG. The levels of both XO and MDA in the spinal cord were increased in SNL rats compared to sham. Intrathecal EGCG decreased the level of XO and MDA. CONCLUSIONS: EGCG may reduce neuropathic pain by SNL due to the suppression of ROS in the spinal cord.